Innovative Approaches for Promoting Resilience, Inclusion and Access to Education Amidst Covid-19 Pandemic in Kenya - Kirimi, Francis; Muthee, Jesca; Gichuhi, Zipporah (Machakos University Press, 2022)
Education has the potency to not only initiate but sustain change for development of an individual and the society at large. As such, education needs to be accessible and inclusive to all members of society regardless of their social and economic status. Education that is accessible to all, has the potency to usher in unending returns and benefit to individuals and society at large. Kenya has recently commenced implementation of competence-based education curriculum which is geared towards empowering her citizens with innovative skills and competencies for development of self and society. Nevertheless the outbreak of COVID-19 pandemic, education in Kenya has been in an awkward and precarious situation in terms of access and inclusion by all learners in the country. Numerous initiatives have been adopted by governments to mitigate the spread of the pandemic as an immediate solution to the pandemic. This paper explores various innovative approaches that educational institutions, communities and the government can institute in order to increase access and promote inclusion of all members from different societal backgrounds and essentially build resilience and promote retention and completion amidst pandemics which have become more of a norm than exception. The proposed approaches will revolve around individuals ,communities and society to identify and customise good practices that can be able to sustain resilient against COVID-19 and other related pandemics
Keywords: Access; Education; Inclusion; Innovation; Pandemics; Resilience